O-257 The effect of the presence of intramural myomas smaller than 6 cm on reproductive outcome in IVF treatment: a systematic review and meta-analysis. (30th June 2022) - Uyanık, E; Erden, M; Tez, R. Cosar; Zaim, O.C; Polat, M; Mumusoglu, S; Yarali, H
Abstract: Study question: What is the effect of small intramural myomas on the reproductive outcome of in vitro fertilization (IVF) treatment? Summary answer: Non-cavity-distorting intramural myomas with the size of < 6 cm have a significant adverse effect on reproductive outcomes in IVF treatment. What is known already: There is a consensus that submucous myomas have a significant unfavorable impact on reproductive outcomes, whereas subserosal myomas do not seem to have any adverse effects. Women with large (≥6 cm) non-cavity-distorting intramural myomas should be evaluated individually, considering their reproductive history. However, there is scarce data on the effect of relatively smaller intramural myomas (<6 cm) on reproductive outcomes and how to manage them before IVF treatment. Study design, size, duration: This study is a systematic review and meta-analysis according to PRISMA guidelines. We performed a comprehensive search of PubMed, Web of Science, and Cochrane Library databases to identify relevant studies from inception until 31 November 2021. Search terms were used as "intramural fibroid*" [tw] OR "intramural leiomyom*" [tw] OR "intramural myom*" [tw]. English language and human subjects were applied to search filters. Participants/materials, setting, methods: The target population was infertile women undergoing IVF treatment with non-cavity-distorting intramural myomas <6 cm in diameter. History of myomectomy and the presence of predominant subserous myomas, submucous myomas, or other cavity distorting pathologies were exclusion criteria. The primary outcome measures were live birth rate (LBR) and miscarriage rate (MR). Newcastle-Ottawa Scale (NOS) was used to assess the methodological quality of included studies. All statistical analyses were performed using RevMan 5.4.1. Main results and the role of chance: The initial search strategy yielded 378 studies. After adopting exclusion criteria, eight studies were included in the final analysis. Six of these studies had a NOS score of 8 out of 10, and the remaining two studies had 9 out of 10. Three studies had a prospective design, and five studies had a retrospective design. Two of eight studies did not report LBR as an outcome. In pooling data analysis of six studies including 2058 cycles (1980 women), 41% relative reduction in LBR was observed in women with non-cavity-distorting intramural myomas with the size of < 6 cm compared to women without myomas (RR = 0.59, 95%CI: 0.49–0.71, I 2 =0%,  p<0.00001). A sub-group analysis for smaller intramural myomas (<3 cm) was also performed and concordantly 27% decrease in the LBR (RR = 0.73, 95% CI: 0.57–0.93, I 2 =0%,  p=0.01) was found. Regarding the MR, for women with non-cavity-distorting intramural myomas with the size of < 6 cm, 50% relative increase in MR was found when compared with women without myomas (RR = 1.50, 95%CI: 1.11–2.04, I 2 =0%,  8 studies,  p=0.009). Limitations, reasons for caution: Lack of information regarding the distance of myomas from endometrium and the number of myomas in most of the included studies is a limitation. Differences in IVF treatment and uterine cavity evaluation methods among studies may limit generalizability of the findings. Future RCTs are warranted to confirm our findings. Wider implications of the findings: This study is the first meta-analysis with overall moderate-quality evidence from observational studies to demonstrate the adverse effect of the presence of small (<6 cm) intramural myomas on reproductive outcomes in IVF treatment. Surgical removal of such small myomas should be considered before IVF treatment. Trial registration number: not applicable